International GAAP 2013 : generally accepted accounting practice under International financial reporting standards - Beyersdorff, Martin; Ernst & Young. International Financial Reporting Group (Chichester, West Sussex : Wiley, 2013)
This set goes much further than explanation. It provides a comprehensive guide to interpreting and implementing IFRS, sets IFRS in a relevant business context and provides insights into how complex practical issues should be resolved in the real world of global financial reporting. This book is an essential tool for anyone applying, auditing, interpreting, regulating, studying or teaching international financial reporting. Written by financial reporting professionals from the International Financial Reporting Group of Ernst & Young, this three-volume guide to reporting under IFRS provides a global perspective on the real-world interpretation and practical application of IFRS.
'The International financial reporting group of Ernst & Young'--Cover.
'Financial instruments and insurance contracts'--Cover of volume 3.
In slip case.
Includes index.
Keywords: International financial reporting standards; Accounting -- Standards; Financial statements